1981
DOI: 10.1021/bi00520a037
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of bromophenol blue and related dyes with bovine neurophysin-I: use as a probe of neurophysin chemistry

Abstract: The interaction of bromophenol blue and related dyes with bovine neurophysin-I was studied by equilibrium dialysis and gel filtration, absorption and circular dichroism spectroscopy, and analytical ultracentrifugation. Binding isotherms for bromophenol blue showed positive cooperativity, with one strong site and one or more weaker sites present per polypeptide chain at pH 4 and an apparent increase in relative importance of the weaker sites of lower pH. Circular dichroism (CD) studies suggested displacement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…Interaction of the bromophenol blue with NP was first suggested by the fact that the degree of electrophoretic separation of different rat neurophysins was dependent on concentration of bromophenol blue as a tracking dye (Burtford and Pikering, 1972). One study showed that dye was bound predominantly to the dimeric form of the protein, based on ultracentrifugation studies (Carlson et al, 1981). However, another study suggested that dye thermodynamically prefers monomer, based on spectroscopically derived binding isotherms (Pearlmntter, 1979).…”
Section: Dye Bromophenol Bluementioning
confidence: 99%
See 3 more Smart Citations
“…Interaction of the bromophenol blue with NP was first suggested by the fact that the degree of electrophoretic separation of different rat neurophysins was dependent on concentration of bromophenol blue as a tracking dye (Burtford and Pikering, 1972). One study showed that dye was bound predominantly to the dimeric form of the protein, based on ultracentrifugation studies (Carlson et al, 1981). However, another study suggested that dye thermodynamically prefers monomer, based on spectroscopically derived binding isotherms (Pearlmntter, 1979).…”
Section: Dye Bromophenol Bluementioning
confidence: 99%
“…Titration of 2.7 mM NP-I with an increasing concentration of dye were carried out from 1:0.4to1:4 molar ratio at 25 oc and pH 2.3. At pH 2.3, NP-I has the highest affinity for bromophenol blue (Carlson et al, 1981). Figure 25 shows the spectrum of 1 mM bromophenol blue at pH 2.3.…”
Section: Dye Bromophenol Bluementioning
confidence: 99%
See 2 more Smart Citations
“…(46, SO)] and by marked similarities in most other properties. The single clear exception to this generality is the reaction of bovine neurophysin-I (oxytocin associated) with bromophenol blue, which is not paralleled by the vasopressin-associated bovine neurophysin-I1 (56,57). Rat neurophysins also appear to differ among themselves in reactivity towards bromophenol blue (58), but it has not been established whether this apparent difference between classes of neurophysins can be generalized.…”
Section: A Comparative Neurophysin Propertiesmentioning
confidence: 99%